Relación de valores de colesterol sérico con las medidas antropométricas en pobladores adultos de Río Seco, Distrito El Porvenir, Abril 2018 - Moreno Cruz, Jilmer Yhsnel (2018)
In the present work, the relationship of serum cholesterol values with anthropometric measurements was determined in adult settlers of Río Seco, El Porvenir District, April 2018. Participants were 44 adult inhabitants of Río Seco. Before their inclusion, they were given a fact sheet, signed the informed consent and obtained the anthropometric measurements: weight (Kg), height (cm) and body mass index (IMC). Blood samples were taken by puncture of the arm, total cholesterol was determined (enzymatic method). The values obtained were as follows: 54,5% had decreased levels of total cholesterol; 36,4% normal levels and 9,1% increased levels. According to the BMI with overweight, cholesterol levels were 20,9% decreased; 23,3% normal and 4,7% increased; with obesity, cholesterolemia was obtained, 18,6% decreased; 9,3 % normal and 2,3% increased, without statistical significance (x2 = 2,26; p> 0,05). According to age, hypercholesterolemia occurs; 4,5% in the age group of 18-41 and 4,5% in the 66-89 age group without statistical significance (x2 = 7,3; p> 0,05). According to sex, there is hypercholesterolemia 4,5% in women and 4,5% in men being statistically non-significant (x2 = 2,38; p> 0,05). Therefore, it is concluded that there is no relationship between serum cholesterol levels with anthropometric measurements, age and sex of people